Evaluación de las principales condiciones físicas e hidráulicas del pavimento rígido existente en la vía Pallatanga-Cumandá - Guayanlema Sinaluisa, Jhonnatan Cristian (2024)
The main objective of this research study focuses on the detailed evaluation of the rigid pavement of roads at Pallatanga-Cumanda, Ecuador. Highlighting its importance in regional connectivity and economic development. This motivates the need to carry out an integral evaluation that covers both the physical and hydraulic conditions of the pavement. In the physical conditions, special attention is paid to fundamental parameters such as resistance to compression and indirect traction, as well as macro texture, essential elements to ensure the durability and efficiency of the pavement over time. Simultaneously, hydraulic aspects are considered, such as runoff coefficient, among others, with the purpose of guaranteeing road safety and functionality in various climatic conditions. In the execution of this research, the coring technique is highlighted as an essential method to obtain representative samples of the pavement, thus allowing an exhaustive evaluation of its current condition. The results obtained are expected not only to provide a detailed understanding of the current situation of the Pallatanga-Cumanda| road, but also to set a precedent for future research